Comparative study of video streaming services: OTT AND IPTV (Revista Científica Interdisciplinaria Investigación y Saberes, 2022)
The purpose of this study is to compare Over-The-Top (OTT) andInternet Protocol Television (IPTV) services, the former consists of thetransmission of audio, video and other types of content over theInternet, while the IPTV service is the one that transmits audio andvideo over IP protocols. The advantages of OTT and IPTVtechnological systems, protocols for their operation, and a briefreview of the hardware required for implementation are presented.The methodology used in the study is bibliographic documentary, theinformation obtained for the constitution of the conceptual theoreticalframework was obtained from specialist. The results allow to evidencethat in Ecuador most citizens have a TV and smartphone in theirhomes, more than half of the population has Internet connectionpermanently, the evolution of the use of OTT and IPTV exacerbatedby the confinement due to the health emergency, are inputs that allowus to conclude that video streaming services: OTT and IPTV constitutean alternative for users, due to the accessibility they present of thecontent to the user.